On the Problem of Determination the Status of a Minor Victim in the Russian Criminal Legislation - Inna Aleksandrovna Kuznetsova; Anatolyi Vladimirovich Kuznetsov (Сибирское юридическое обозрение, 2012)
In the article the authors deal with the problem of the determination the status of the person under-age as a victim in the Russian criminal legislation. The authors offer the ways to solve the problem.